A New Rat Model of Chronic Cerebral Hypoperfusion Resulting in Early-Stage Vascular Cognitive Impairment - Wang, Jinxin; Yang, Chenyi; Wang, Haiyun; Li, Dongxue; Li, Tang; Sun, Yi; Zhao, Mingshu; Ma, Ji; Hua, Wei; Yang, Zhuo (Frontiers in Aging Neuroscience, 2020)
Objective Currently, most models of vascular cognitive impairment are established by occluding the carotid arteries uni- or bilaterally to reduce the cerebral blood flow mimicking chronic cerebral hypoxia. Due to the sudden blood flow interruption, a gradual narrowing of the carotid artery cannot be completely imitated. This paper aims to establish a bilateral carotid stenosis model with mild cognitive dysfunction and mild white matter changes to simulate patients with vascular predementia. Methods Aged Wistar rats (18 months old) underwent either bilateral common carotid artery stenosis (BCAS) or occlusion (BCAO) surgery or a sham operation (control group). The cerebral blood flow in the frontal cortex was measured using Doppler flowmetry. Thirty days after surgery, cognitive function impairments were determined with the Morris water maze; cerebral magnetic resonance imaging was performed to detect changes in fractional anisotropy to assess white matter injuries, and histological studies were performed. Results The aged rats in the BCAS group showed a more gradual cerebral blood flow reduction and a lower mortality rate (11%) compared to rats in the BCAO group. The water maze test revealed a more marginal impairment affecting spatial learning and memory in rats with BCAS than in rats with BCAO. Diffusion tensor imaging detected white matter injuries in the hippocampus and cerebral cortex of BCAS rats. Particularly, a small portion of nerve fibers of the lateral somatosensory cortex was significantly different between rats of the BCAO and BCAS groups. In the BCAS group, the microscopic structure of the hippocampal CA1 region changed slightly after 30 days and sustained a slight mitochondrial crista crack. Fluorescence staining indicated that the number of GFAP-positive cells was increased in rat brains of the BCAS group, and this phenomenon was even more pronounced in the BCAO group. The hnRNPA2/B1 and GABAAR-α1 expression levels were significantly decreased in the hippocampus of rats with BCAS compared to those of controls. Conclusion Severe bilateral carotid stenosis induced mild cognitive dysfunction and slight structural changes in the brains of aged rats. Thus, a chronic cerebral hypoperfusion model was successfully established.